PENGARUH DINAMIKA INTERNAL PARTAI TERHADAP STRATEGI POLITIK PARTAI AMANAT NASIONAL PASCA KONGRES IV TAHUN 2015 - Ratnia Solihah (JWP (Jurnal Wacana Politik), 2016)
Internal conflict within a political party commonplaces in political institutions, especially in the context of fighting for power or leadership in a party. But internal conflicts in the electoral process currently Chairman of the PAN congressional IV in Bali in 2015 does not lead to a prolonged conflict until the dualism of leadership of a party or departure of chairman candidate who lost in the political competition by setting up a new political party. Post-election of Chairman of the National Mandate Party Zulkifli Hasan replacing Hatta Rajasa. Raises the political dynamics of internal new has happened in the PAN, which also affects changes in political strategy PAN good political strategy for the internal PAN and external PAN, which aims to increase the capabilities of the party, the public trust/ society against the PAN and to improve electability PAN in elections in 2019.